Demographic changes in primiparae of Irish ethnicity between 2000 and 2020. (November 2022) - Shah, A.; Farah, N.; McNamee, E.; Lindow, S.W.; O'Connell, M.
Abstract: Background: Trends in maternal demographic changes linked to lifestyle and socio-economic conditions reflect greatly on maternal, perinatal and infant mortality rates. Hospital data reflect a heterogenous population where specific demographic changes may not be obvious. Objectives: To report yearly demographic changes in Irish primiparae from 2000 to 2020, specifically looking at age, BMI, smoking and marital status of patients attending the Coombe Women and Infant's University Hospital (CWIUH). Methods: Retrospective report of demographic details contemporaneously documented on the CWIUH data base. Findings: In the years 2000 to 2020 inclusive there were 47, 659 primiparous women of Irish ethnicity delivered at the CWIUH (70.2% of the total primiparae), of those 99.3% were Caucasian. There was a significant rise in mean age at first delivery in Irish mothers; 26.0 years old in the 2000 to 30.9 years old in 2020 associated with a rise in mean BMI of 9.1%. Smoking rates (ever smoked) showed a significant reduction from 53.9% in 2000 to 39.3% in 2020. There was a significant decrease in rates of marriage, with 61.9% married in 2000 compared to 46.3% in 2020. Birth weight and prematurity rates remained unchanged, with fall in mean gestational age at first delivery from 279.3 days in 2000 to 275.8 days in 2020. Conclusion: This study highlights that Irish primiparae are older, heavier, less likely to smoke and to be married than they were 20 years ago. These trends are an interesting glimpse into changing economic and cultural climate over just the past 2 decades.